The Educational and Social World of a Child. Discourses of Communication, Subjectivity and Cyborgization - (:unkn) unknown (Adam Mickiewicz University Press, 2015)
The book comprises nearly 50 texts written by Polish, American and Israeli researchers into the child’s world and show the complexity of this world and underline the contemporary categories of its oscillation: discourses of communication, subjectivity and cyborgization. The texts are ordered into 3 parts, each of which devoted to a different contemporary axis of oscillation of the child’s world. To bring order to the debate on the child of today, we have searched for categories that on the one hand would break with the schematic character and stereotypes in describing the child’s reality, and on the other hand would present the actual, undetached from everyday life, space of life of the contemporary child. We also wanted them to be able to cover new phenomena, new ways of assigning meanings and new strategies for the construction and reconstruction of the life of a child that we observe in the world of today.
Edukacyjny i społeczny świat dziecka. Dyskursy komunikacji, podmiotowości i cyborgizacji
Keywords: children; education; communication; subjectivity; cyborgization; ICT